2010
DOI: 10.1055/s-0029-1243883
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of Barrett’s esophagus: outcomes of 429 patients from a multicenter community practice registry

Abstract: In this multicenter registry conducted at four community-based practices, the observed safety and efficacy outcomes associated with RFA for Barrett's esophagus are comparable to those previously reported in multicenter trials from predominantly tertiary academic centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
1
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 43 publications
(23 reference statements)
7
92
1
4
Order By: Relevance
“…Shaheen et al reported that at 3 years dysplasia remained eradicated in >85% of patients and intestinal metaplasia in >75% [43], but this data also revealed a persistent risk of cancer in some patients, although perhaps the overall risk of cancer was reduced across the whole cohort. Lyday et al (2010) also found complete remission of non-dysplastic Barrett's esophagus in 77% of patients (n = 137) at 20 months follow up [36], and Ganz et al (2008) found a 54% complete remission rate for non-dysplastic Barrett's esophagus at median 12 months follow up [37].…”
Section: Endoscopic Ablationmentioning
confidence: 96%
See 1 more Smart Citation
“…Shaheen et al reported that at 3 years dysplasia remained eradicated in >85% of patients and intestinal metaplasia in >75% [43], but this data also revealed a persistent risk of cancer in some patients, although perhaps the overall risk of cancer was reduced across the whole cohort. Lyday et al (2010) also found complete remission of non-dysplastic Barrett's esophagus in 77% of patients (n = 137) at 20 months follow up [36], and Ganz et al (2008) found a 54% complete remission rate for non-dysplastic Barrett's esophagus at median 12 months follow up [37].…”
Section: Endoscopic Ablationmentioning
confidence: 96%
“…This mucosa is histopathologically similar to normal squamous epithelium, and it has therefore been assumed to have a reduced risk of cancer [22,23]. A variety of different ablation techniques have been developed, including argon plasma coagulation (APC) [24][25][26][27], photodynamic therapy (PDT) [28][29][30], multipolar electrocoagulation (MPEC) [31,32], Nd:YAG (neodymium-doped yttrium aluminum garnet) laser therapy [33][34][35], and more recently radiofrequency ablation (RFA) [36,37].…”
Section: Endoscopic Ablationmentioning
confidence: 99%
“…Bleeding requiring endoscopic therapy occur in less than 2% and strictures in 2-8%, perforation has also been reported [63,64].…”
Section: Ablation Techniquesmentioning
confidence: 97%
“…The available data from prospective trials are summarized in Table III (123,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156).…”
Section: Radiofrequency Ablation (Rfa)mentioning
confidence: 99%